Caries profile of metropolitan and regional Australian primary school children - Mr Sahib Rekhi; Mr Adam Lits; Mr Navjot Brar; Ms Karen Lansdown; Dr Smitha Sukumar (Elsevier, 2023)
Aim or Purpose: To analyse the caries status of primary school children in metropolitan and regional New South Wales (NSW) and regional Victoria. Materials and Methods: Ethics approval was obtained from The University of Sydney (HRECS 2022/839) to analyse the anonymized oral health data of 841 primary school children collected by the community outreach program, Carevan Sun Smiles in 2019. This retrospective case-cohort study investigated caries status of children at each school using ICDAS II scores. Analysis was undertaken based on age with four groups created - Group 1 (Kindergarten/Year1), Group 2 (Year 2/3), Group 3 (Years 3 and 4) and Group 4 (Years 5 and 6). The Kruskal-Wallis rank sum test was undertaken to compare ICDAS scores between schools for each age group. Results: The school with the highest caries burden (mean ICDAS II score = 1.45) and the biggest range in scores (ICDAS 1 - 1.68) was the regional Victorian school compared to both NSW schools (mean score of 1.40, ICDAS 1.27 - 1.5). However, this difference in school means was not statistically significant (Kruskal Wallis p=0.37). Furthermore, we found no statistical difference in mean ICDAS II score in all age groups between the three schools. Conclusions: Our results indicate that Australian regional communities may carry a heavier burden of tooth decay and this is consistent with the literature. While larger studies are required to provide more definitive results, access to preventive dental care remains a priority for primary school children to minimize treatment required and ensure long term oral health.